Managerial overconfidence and dividend policy in Vietnamese enterprises - Nguyen Dat Dinh; To Tha Hien; Nguyen Duy Van; Huyen Phuong Do (Cogent Economics & Finance, 2021)
The dividend policy in an enterprise depends not only on the company's strategy but also on the characteristics of the managers. In particular, the element of overconfidence of the CEO contributes to the decision-making process for the dividend. Therefore, this study is conducted to determine the effect of overconfident CEO on dividend policy through dividend yield and dividend payout. The study carried out an evaluation based on 576 companies listed on Vietnam's stock market from 2014 to 2018. Panel data model with GLS (error correction model) is used in regression analysis. The analysis results show that CEO overconfidence has a positive impact on Dividend Payout and Dividend Yield. At the same time, the study also shows that the influence of CEO overconfidence on Dividend Payout is the same between state-owned and non-state enterprises and companies listed on different exchanges (HNX and HOSE). In addition, the results also indicate that there is no influence of CEO overconfidence on Dividend Yield in state-owned enterprises as well as companies listed on the HOSE. From the research results, the author also made some conclusions and recommendations for managers and investors.
Keywords: B26; C33; G40; 330; CEO overconfidence; dividend payout; dividend yield; Managerial overconfidence